Effective utilization of attentional resources in postural control in athletes of skill-oriented sports: an event-related potential study - Chen, Jiacheng; Kwok, Alex Pak Ki; Li, Yanan (Frontiers in Human Neuroscience, 2023)
Objective: Postural control plays a key role in skill-oriented sports. Athletes of skilloriented sports (hereinafter referred to as "skilled athletes") usually showed better control ability compared with nonathletes. However, research focused on the single postural task, rarely considering the actual situation in skill-oriented sports in which other processes, such as cognitive control, frequently accompany postural control. This study aims to explore how skilled athletes control their posture under the dual-task situation and use limited attentional resources.Method: 26 skilled athletes and 26 nonathletes were required to perform the postural control and N-back tasks simultaneously. Center of pressure (COP) trajectory, reaction times (RTs), and discriminability (d') of N-back tasks were recorded and evaluated, along with event-related potentials, including N1 (Oz, PO7, and PO8), P2 (Fz, FCz, Cz, and Pz) components, and the spectral power of alpha band.Results: Skilled athletes demonstrated more postural control stability and a higher d' than nonathletes in all dual tasks. Besides, they showed enhanced N1, P2 amplitudes and reduced alpha band power during dual-tasking. Notably, in skilled athletes, a significant negative correlation between N1 amplitude and d' was observed, while significant positive correlations between alpha band power and postural control performance were also identified.: This study investigates the potential advantages of skilled athletes in postural control from the view of neuroscience. Compared to nonathletes, skilled athletes could decrease the consumption of attentional resources in postural control and recruit more attentional resources in stimulus discrimination and evaluation in cognitive tasks. Since the allocation of attentional resources plays a crucial part in postural control 2 in skilled athletes, optimizing the postural control training program and the selection of skilled athletes from a dual-task perspective is important.